Assessing the Suitability of Next-Generation Viral Outgrowth Assays to Measure Human Immunodeficiency Virus 1 Latent Reservoir Size. (9th March 2020) - Stone, Mars; Rosenbloom, Daniel I S; Bacchetti, Peter; Deng, Xutao; Dimapasoc, Melanie; Keating, Sheila; Bakkour, Sonia; Richman, Douglas D; Mellors, John W; Deeks, Steven G; Lai, Jun; Beg, Subul; et al.
Abstract: Background: Evaluations of human immunodeficiency virus (HIV) curative interventions require reliable and efficient quantification of replication-competent latent reservoirs. The "classic" quantitative viral outgrowth assay (QVOA) has been regarded as the reference standard, although prohibitively resource and labor intensive. We compared 6 "next-generation" viral outgrowth assays, using polymerase chain reaction or ultrasensitive p24 to assess their suitability as scalable proxies for QVOA. Methods: Next-generation QVOAs were compared with classic QVOA using single leukapheresis-derived samples from 5 antiretroviral therapy–suppressed HIV-infected participants and 1 HIV-uninfected control; each laboratory tested blinded batches of 3 frozen and 1 fresh sample. Markov chain Monte Carlo methods estimated extra-Poisson variation at aliquot, batch, and laboratory levels. Models also estimated the effect of testing frozen versus fresh samples. Results: Next-generation QVOAs had similar estimates of variation to QVOA. Assays with ultrasensitive readout reported higher infectious units per million values than classic QVOA. Within-batch testing had 2.5-fold extra-Poisson variation (95% credible interval [CI], 2.1–3.5-fold) for next-generation assays. Between-laboratory variation increased extra-Poisson variation to 3.4-fold (95% CI, 2.6–5.4-fold). Frozen storage did not substantially alter infectious units per million values (−18%; 95% CI, −52% to 39%). Conclusions: The data offer cautious support for use of next-generation QVOAs as proxies for more laborious QVOA, while providing greater sensitivities and dynamic ranges. Measurement of latent reservoirs in eradication strategies would benefit from high throughput and scalable assays. Abstract : We demonstrated similar estimates of variation for classic and next-generation quantitative viral outgrowth assays (QVOAs), with enhanced sensitivity supporting the use of next-generation QVOAs as a proxy for classic QVOAs in measuring the latent human immunodeficiency virus reservoir.